The Influence of Viral Marketing And Electronic Word of Mouth (E-Wom) on Purchase Decisions For Cimory Yogurt Bites Products in Tiktok Shop - Rangga Rangga; Puji Isyanto; Neni Sumarni (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to analyze the impact of viral marketing and electronic word of mouth (e-WOM) on purchasing decisions for Cimory Yogurt Bites products through TikTok Shop. By applying a quantitative descriptive verification approach and the Partial Least Square-Structural Equation Modeling (PLS-SEM) method, data was collected from 105 respondents who are active TikTok Shop users. The results revealed that viral marketing contributes significantly to purchasing decisions through the rapid and engaging dissemination of information on social media. Similarly, e-WOM provides a significant positive impact through consumer reviews that increase trust in the product. Together, these two variables explain 83.3% of the variability in purchase decisions. The findings confirm the importance of social media-based marketing strategies in attracting the attention of consumers, especially the younger generation. This research provides strategic insights for businesses to optimize the use of social media to increase product appeal and sales.